Quantification of Minerals in Edible Mushrooms via Optimized Microwave-Assisted Digestion: Nutritional Contributions of Fe, Mg, Na, K, and Ca - Alejandro R. López; Elena Ortega-Caneda; Estrella Espada-Bellido; Oscar R. Taracena-Zepeda; Miguel Palma; Gerardo Fernández-Barbero (Foods)
The intake of mushrooms provides numerous beneficial properties for the correct functioning of the human body due to their rich content in carbohydrates, proteins, fibers, vitamins, and minerals. However, most of the reports are focused on the determination of bioactive compounds and only a few regarding the essential mineral content and the evaluation of the RDI. Thus, the aim of this study was to determine the mineral composition of different cultivated (A. bisporus and P. ostreatus) and wild edible mushrooms (A. crocodilinus, A. arvensis, A. silvicola, A. impudicus, M. mastoidea, M. rhacodes, and P. ostreatus) collected in the south of Spain and north of Morocco. First, the optimization of a microwave-assisted digestion method was carried out using a Box–Behnken design with a response surface methodology to quantify the total content of five metals: Fe, Mg, Na, K, and Ca in mushrooms. The samples were analyzed by FAAS and ICP-OES. The percentage of the RDI of each mineral covered by the intake of mushrooms was calculated. It was observed that a high percentage of RDI levels are covered and just exceeded for Fe. Thence, due to their beneficial properties and high content of essential minerals, mushrooms would be proposed as a valuable source of nutrients to manufacture some food supplements.